Palladium(II)-Catalyzed C–H Activation and C–C Coupling/Cyclization of Benzamidine and Terminal Alkynes Using an Internal Oxidant - Zhang, Xu; Xu, Xuefeng; Wu, Yingke; Wang, Zhiqiang; Yu, Lintao; Zhao, Qiang; Shi, Fu (Synlett, 2015)
Herein, an efficient palladium(II)-catalyzed C–C coupling/cyclization reaction by directed C–H activation of benzamidine and terminal alkynes has been developed. In this practical and high-yielding process, the C–N bond acts as an internal oxidant. It was found that molecules with both electron-donating and electron-withdrawing substituents were suitable substrates for this transformation, and the expected products were obtained in moderate to excellent yields, but when the benzamidine with ortho-methyl substituent is employed, the benzamidine compound may undergo the [1,5]-hydrogen migration, and then Diels–Alder reaction with terminal alkynes to produce the quinoline compound. The use of a single catalytic system to mediate chemical transformations in a synthetic operation is efficient in building complex structures from simple starting materials in an environmentally benign fashion.
Keywords: C–H activation; internal oxidant; C–C bond coupling; terminal alkynes